Exploring Contemporary Islamic Economic Thought In Indonesia - Rani Mariana; Yadi Janwari; Ahmad Hasan Ridwan (al-Afkar, Journal For Islamic Studies, 2023)
This study aims to analyze contemporary Islamic economic thought in Indonesia from the initial phase of the formation of Islamic economics in the time of the Prophet to Indonesia and analyze the thoughts of contemporary Islamic economic figures, such as Adiwarman A. Karim and Syafi'i Antonio. This research uses descriptive qualitative method based on library research. The results of this study indicate that contemporary Islamic economic thought figures in Indonesia belong to one of the three schools of thought of contemporary Islamic economics, such as the Baqir Ash Sadr school, the mainstream school, and the alternative school.